Liikunnan sosiaalipolitiikka - Uusi-Illikainen, Marika (2024)
Uusi-Illikainen, M. 2024. Social policy of sport. Faculty of Sport and Health Sciences, University of Jyväskylä, Master’s thesis in the Social Sciences of Sport, 104 pp., 0 appendices.